NEUROMUSCULAR TAPING TEKNIK KOMPRESI MENINGKATKAN EXPLOSIVE POWER DAN MAXIMUM SPEED LARI 100 METER - Utami, Tri Setyo; Purwanto, Bambang; Mintarto, Edy (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Sprint 100 meter that has sprint phase such as acceleration, maximum speed, and deceleration which can improvement performance in sprinting ability. The aim of this study to showing effect of neuromuscular taping compression technique on explosive power and sprint 100 meter to provide increased muscle functional ability, tendon efficiency, and joint stability by stimulating the nerves. This study is an experimental research field with a pre-test and post-test control group design. Twenty-two samples were selected from the population of East Java sprint athletes based on the consecutive sampling technique which was divided into two groups randomly. Neuromuscular compression technique are given Intervention in the gastrocnemius area on treatment group after pre-test. The explosive power are using tandem vertical jump test measurenment and infared electrics time respectively.The paired sample T-test are showing increases in expolsive power in the gastrocnemius and sprint 100 meter maximum phases (p